Answer:
The answer is yes , k = -2 and y = -2x ⇒ first answer
Explanation:
* To prove the variation
- Check the constant change in the values of x and y
- Lets check that from the table
# At x = 1 ⇒ y = -2
# At x = 3 ⇒ y = -6
# At x = 5 ⇒ y = -10
* -6 - -2 = -6 + 2 = -4 ⇒ 3 -1 = 2
-10 - -6 = -10 + 6 = -4 ⇒ 5 - 3 = 2
∴ y decreased by 4 when x increased by 2
* This is a constant change
∴ y is varies directly with x
∴ y ∝ x
∴ y = k x ⇒ where k is the constant of the variation
* Lets find the value of k
- You can use one value of x and y from the table
∵ x = 3 and y = -6
∴ -6 = k (3) ⇒ divide two sides by 3
∴ k = -2
∴ The equation of the variation is = y = -2x
* The answer is yes , k = -2 and y = -2x